Electrical stunning effectiveness with current levels lower than 1 A in lambs and kid goats. (February 2015) - Llonch, P.; Rodríguez, P.; Casal, N.; Carreras, R.; Muñoz, I.; Dalmau, A.; Velarde, A.
Highlights: The effects of system and intensity on stunning effectiveness in lamb were assessed. Stunning with 0.3, 0.5, 0.7 and 1.0 A provoke instant unconsciousness in all lambs. Extent of unconsciousness is not different using 0.3, 0.5 and 0.7 compared to 1.0 A. Fewer lambs recover before death in HB compared to HO stunning. Abstract: An experiment with 360 lambs grouped into three Spanish commercial categories, (Pascual, 13–16 kg; Recental, 9–13 kg and Lechal <7 kg carcass weight) and kid goats (7 kg) was performed to assess stunning effectiveness after head-only (HO) and head-to-body (HB) electrical stunning with intensity currents of 0.3, 0.5 and 0.7 Amperes (A) compared to 1.0 A. After stunning, all animals showed tonic-clonic muscular activity and epileptiform EEG, absence of rhythmic breathing, corneal reflex, spontaneous blinking and pain sensibility. The quiescent EEG occurred earlier (P < 0.05) in HB compared to HO in all categories. More animals recovered corneal reflex and rhythmic breathing before onset of the quiescent activity after HO (from 15 to 50%) compared to HB (from 0 to 15%) (P < 0.05). Concluding, HO and HB electrical stunning with 0.3, 0.5 and 0.7 A induce effective stunning similar to 1.0 A in lambs and kid goats. After stunning and sticking, brain failure occurs earlier in HB than HO system.